In-depth and Comprehensive Analysis of Divorce Cases Due to Domestic Violence from a Family Law Perspective - Tarina, Dwi Desi Yayi; Syarief, Rose Esperahanna Tiara; Salamah, Ajeng Prameswari; Aulia, Saffira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Domestic violence is one of the reasons that can be used to file for divorce in family law in Indonesia. However, the process of proving violence often poses a huge obstacle and becomes a very serious problem for the party applying for divorce. In this article, we will analyze in depth, thoroughly and comprehensively a divorce case based on domestic violence from the perspective of family law in Indonesia. We will examine in detail, in detail and in great detail the evidence presented, the legal basis used, and the judge's considerations in deciding this case. Apart from that, we will also look at the impact of this decision on the development of family law in Indonesia in a very deep, thorough and comprehensive manner. In its considerations, the panel of judges stated that based on the evidence presented, it was legally and convincingly proven that the Defendant had committed physical and psychological violence which was categorized as